Development of a Local Wisdom Based Self-Esteem Scaffolding Model to Improve Elementary School Students' Social Skills - Rizka Novi Irmaningrum; Oriza Zativalen; Ari Susandi; Humairah Humairah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background: Students' social competence tends to be lacking in the learning process. Students are lacking in communication, even do not appear to empathize, appreciate differences, and resolve conflicts positively. Teachers often use the lecture method and do not use a guided learning model related to self-esteem. Students lack local wisdom in instilling in the character of elementary school students. Aim: to develop a learning model related to student self-esteem, namely the Self Esteem Scaffolding model. This model will be developed with local wisdom that shows collaboration supported by local cultural values with teacher guidance. Method: a development model adapted from Plomp (1997). The development model adapted by Plomp has five main stages, namely: (1) Initial investigation or initial study; (2) Design, (3) Realization/Construction; (4) Expert validation test, trial, evaluation, and revision; and (5) Implementation. Based on the results of the initial study, a design of the Local Wisdom-Based Self Esteem Scaffolding model was prepared. The model design in this study includes: (1) model book design; (2) learning component design (student books, teaching modules, LKPD); and (3) instrument design to obtain data in the model development process. Results and Discussion: The development of the Local Wisdom-Based Self Esteem Scaffolding model has been tested for validity with a percentage result of 91% and a practicality result of 93%. The learning model design used, namely the local wisdom-based self-esteem scaffolding model on the topic of Lamongan City Cultural Values, proves that the learning model related to local wisdom is able to improve students' social skills as evidenced by an increase from cycle I of 47.3% and cycle II of 91.7%. Conclusion: the development of the Local Wisdom-Based Self Esteem Scaffolding Model is considered feasible and can improve students' social skills.